PENGEMBANGAN BAHAN AJAR BERBASIS VIDEO UNTUK PESERTA DIDIK MAUPUN PENDIDIK TINGKAT SMA SEDERAJAT DAN DIBAWAH - Haryadi, Rudi; Kinanti, Sekar Nurfitta (EduFisika: Jurnal Pendidikan Fisika, 2022)
This article examines more profoundly the relationship between the development of teaching materials using learning videos and the learning outcomes of a subject for high school/vocational high school students and below; thus, the purpose of this article is to make readers aware of the benefits of using video in learning such as the effectiveness of videos in terms of making and exposure, the level of interest of students, learning outcomes, motivation, and critical thinking. The method used in this study is to analyze several journals related to developing learning video-based teaching materials through the Google Scholar site, then sum every journal, such as research methods, research results, and conclusions. From these journals, it was concluded that research results showed (1) the use of learning videos was able to improve student learning outcomes, (2) students became active in asking questions and following the learning process using teaching materials based on learning videos and those that had been provided, ( 3) unique learning videos can be made easily by educators of all ages using computer applications, (4) the application of video-based learning media is categorized as feasible to improve students' critical thinking skills.